Magnetic filler, production method of the same, and magnetic filler-containing resin composition
Patent Information
- Application Number
- JP2023136188
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-03-07
AI Technical Summary
【0022】 本発明によれば、優れた磁気特性を有するフェライト粒子、及び磁気特性ならびにハンドリング性に優れた該フェライト粒子含有樹脂組成物を提供できる。また、当該フェライト粒子を容易に製造することができるフェライト粒子の製造方法を提供できる。
Smart Images

Figure 2025030682000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic filler, a method for producing the same, and a magnetic filler-containing resin composition. [Background technology]
[0002] In recent years, the demand for noise suppression sheets has been expanding due to the increasing density of electromagnetic environments inside automobiles and other vehicles caused by the electrification of these vehicles. Currently, most noise suppression sheets are for car navigation systems and in-vehicle cameras, but demand is expected to grow for millimeter wave radars in the future. In addition, in the communications field, the shift to 5G is creating an increasing demand for high shielding performance in noise suppression sheets for smartphones.
[0003] Conventionally, ferrite particles mainly composed of iron oxide (Fe2O3) have been widely developed. For example, Patent Document 1 discloses a ferrite powder consisting of spherical ferrite particles with a specific composition ratio, in which the amount of α-Fe2O3 is more than 0.0 mass% and not more than 7.5 mass%, the spinel phase is 80 mass% or more, and the volume average particle diameter (D50) is 15.0 μm or less. By containing a predetermined amount of α-Fe2O3, the ferrite powder can increase the electrical resistance while maintaining the magnetic properties (saturation magnetization, magnetic permeability) of the ferrite powder at a high level, and when applied to a resin composition, it has the effect of maintaining a high filling rate and a high withstand voltage.
[0004] However, the magnetic properties of the ferrite particles of Patent Document 1 are still insufficient. Generally, magnetic permeability is determined by the magnitude of saturation magnetization. Since saturation magnetization is the difference between the magnetic moment of the metal elements located at the Td site and the Oh site, further improvement in magnetic permeability cannot be expected in the ferrite particles of Patent Document 1 that have one divalent ion.
[0005] To address this issue, two doubly charged ions (e.g., A 0.5 B 0.5 There has been much research into designing ferrite particles of larger diameters (Fe2O4) and larger sizes.
[0006] For example, Patent Document 2 discloses that Ni-Zn ferrite powder having a composition consisting of Fe2O3, NiO, and ZnO and further containing silicon oxide has excellent DC bias characteristics.
[0007] In addition, in Patent Document 3, M x Fe 3-x The present invention discloses ferrite particles represented by O4 (M is at least one metal selected from the group consisting of Mg, Mn, Ca, Sr, Ti, Cu, Zn and Ni, 0≦x≦1), which have a first average particle size in the range of 20 to 30 μm, a shape factor SF-1 (circularity) of on-screen particles after sieving of the ferrite particles is 127 or less, and the proportion of particles having a shape factor SF-1 of 140 or more is 6% or less by number. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent Publication No. 2021-66648 [Patent Document 2] JP 2007-145703 A [Patent Document 3] JP 2016-118646 A Summary of the Invention [Problem to be solved by the invention]
[0009] In general, one of the means for improving the magnetic properties of a ferrite particle-containing resin composition is to improve the packing rate of ferrite particles while maintaining the handleability of the resin composition. However, Patent Document 2 only confirms the magnetic properties of the sintered body, and Patent Document 3 only confirms the durability as a carrier core material of an electrophotographic image forming device, and no sufficient consideration is given to what kind of ferrite particles should be used to improve the content in the resin composition.
[0010] The present invention has been made to solve the above-mentioned problems, and aims to provide ferrite particles that can be highly filled into resin and achieve good handleability, a method for producing the same, and a resin composition that contains the ferrite particles and has excellent magnetic properties. [Means for solving the problem]
[0011] As a result of intensive research to solve the above problems, the inventors discovered that by making ferrite particles with specific particle characteristics, it is possible to achieve a high filling rate while maintaining the handleability of a resin composition, and that when made into a resin composition, the resin composition has excellent magnetic properties, and thus completed the present invention. That is, the present invention has the following aspects.
[0012] (1) A x B y C 1-x-y A ferrite particle represented by Fe2O4 (wherein 0.3≦x≦0.7, 0≦y≦0.3), wherein the metal elements A, B, and C are each independently one element selected from the group consisting of Ni, Mn, Cu, Zn, Mg, Ca, and Co, and the metal element A is an element different from the metal elements B and C, and D of the ferrite particle 50 / D sa Ferrite particles (D sa can be calculated using the following formula (1). D sa =6 / (specific surface area x specific gravity ρ)...(1)
[0013] (2) A x B y C 1-x-yFerrite particles represented by Fe2O4 (where 0.3≦x≦0.7, 0≦y≦0.3), wherein metal elements A, B, and C are each independently one element selected from the group consisting of Ni, Mn, Cu, Zn, Mg, Ca, and Co, and metal element A is an element different from metal elements B and C, and fine particles (D of the entire ferrite particles) adhering to a particle surface of a main particle of the ferrite particles observed from an SEM image are 50 The ferrite particles are characterized in that the average number of particles (whose particle size is 1 / 20 or less relative to the particle size) is 10 or less.
[0014] (3) A x B y C 1-x-y The ferrite particles are represented by Fe2O4 (where 0.3≦x≦0.7, 0≦y≦0.3), wherein the metal elements A, B, and C are each independently one element selected from the group consisting of Ni, Mn, Cu, Zn, Mg, Ca, and Co, and the metal element A is an element different from the metal elements B and C, and fine particles attached to the particle surface of the ferrite particles (D of the entire ferrite particles) are 50 The ferrite particles according to (1) above, characterized in that the number of particles (having a particle size of 1 / 20 or less relative to the particle size) is 10 or less.
[0015] (4) (D 90 -D 10 ) / D 50 The ferrite particles according to any one of the above (1) to (3), wherein the SPAN value determined by the above formula (1) is 0.7 or more and 2.0 or less.
[0016] (5) The ferrite particles according to any one of the above (1) to (4), which have a spinel structure and a polyhedral shape.
[0017] (6) D of the ferrite particles 50 The ferrite particles according to any one of the above (1) to (5), wherein the average particle diameter is 0.1 μm or more and 100 μm or less.
[0018] (7) The method for producing ferrite particles according to any one of (1) to (6) above, wherein the fluxing agent is D 90 A method for producing ferrite particles, comprising using 50 mass% or less of molybdate having a particle size of 1 to 100 μm based on the total amount of raw materials.
[0019] (8) A resin composition containing the ferrite particles according to any one of (1) to (6) above.
[0020] (9) The resin composition according to (8) above, wherein the filling rate of the ferrite particles is 75 wt % or more.
[0021] (10) The resin composition according to (8) or (9) above, wherein the imaginary component μ″ of complex permeability at a frequency of 1.5 GHz is 1.3 or more, or the imaginary component μ″ of complex permeability at a frequency of 7.0 GHz is 0.4 or more. Effect of the Invention
[0022] According to the present invention, it is possible to provide ferrite particles having excellent magnetic properties, a resin composition containing the ferrite particles having excellent magnetic properties and handleability, and a method for producing the ferrite particles, which can easily produce the ferrite particles. [Brief description of the drawings]
[0023] [Figure 1] 1 is a SEM image of the ferrite particles obtained in Example 1. [Diagram 2] 1 is a SEM image of the ferrite particles obtained in Example 6. [Diagram 3] 1 is a SEM image of ferrite particles obtained in Example 9. [Figure 4] 1 is a SEM image of ferrite particles obtained in Comparative Example 1. [Diagram 5] 1 is a SEM image of ferrite particles obtained in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Hereinafter, an embodiment of the present invention will be described in detail.
[0025] <Ferrite particles> The ferrite particles of the present invention are x B y C 1-x-y The ferrite particles have two or three divalent ions represented by Fe2O4. In the formula, A, B, and C each represent a metal element, and each is independently an element selected from the group consisting of Ni, Mn, Cu, Zn, Mg, Ca, and Co. Note that the metal element A represents an element different from the metal elements B and C.
[0026] "Metal element A is an element different from metal elements B and C" means that the ferrite particles have two or three divalent ions. For example, when A is Mn, B and C are each independently one selected from the group consisting of Ni, Cu, Zn, Mg, Ca, and Co, and B and C may be the same element or different elements.
[0027] A typical ferrite particle with two divalent ions is Mn x Mg 1-x Fe2O4, Mn x Zinc 1-x Fe2O4, Ni x Zinc 1-x Fe2O4; Ferrite particles with three divalent ions are Ni x Mn y Zinc 1-x-y Fe2O4, Co x Zinc y Ni 1-x-y Fe2O4, Ni x Cu y Zinc 1-x-y Fe2O4, but is not limited thereto, and all conceivable combinations of Ni, Cu, Zn, Mg, Ca, and Co are possible.
[0028] Ferrite particles that have excellent magnetic properties and exhibit excellent properties when blended with a resin composition described below include Mn x Zinc1-x Fe2O4, Ni x Zinc 1-x Fe2O4, Co x Zinc y Ni 1-x-y Fe2O4 is preferred, Ni x Zinc 1-x Fe2O4, Co x Zinc y Ni 1-x-y Fe2O4 is more preferable. In the case of the ferrite particles, the difference in magnetic moment between the metal elements arranged at the Td site and the Oh site becomes large, and thus the magnetic properties are excellent, which is preferable.
[0029] A x B y C 1-x-y In Fe2O4, x and y are 0.3≦x≦0.7 and 0≦y≦0.3, and more preferably 0.4≦x≦0.7 and 0≦y≦0.3. If they are within the above ranges, the imaginary component μ″ of the complex permeability at high frequencies is large, which is preferable.
[0030] The ferrite particles of the embodiment include A with respect to 100 mass% of the ferrite particles. x B y C 1-x-y The Fe2O4 content is preferably 65 to 99.99 mass%, more preferably 70 to 99.98 mass%, and further preferably 90 to 99.95 mass%.
[0031] The iron content in the ferrite particles can be measured by XRF analysis. The iron content in the ferrite particles of the embodiment is preferably 45 to 85 mass%, more preferably 50 to 80 mass%, and even more preferably 55 to 75 mass%, in terms of Fe2O3 content (Fe1) relative to 100 mass% of the ferrite particles, as determined by XRF analysis of the ferrite particles.
[0032] Hereinafter, the present embodiment will be taken as a representative example of ferrite particles, and the content of each metal element measured by XRF analysis will be shown, but the ferrite particles of the present invention are not limited to these combinations of metal elements.
[0033] As an example of the ferrite particles of the embodiment, a spinel structure is x Zinc 1-x When expressed as Fe2O4, the content of the ferrite particles is determined by XRF analysis of the ferrite particles, relative to 100 mass% of the ferrite particles. The ferrite particles may have a content (Ni1) of 5 to 30 mass%, a content (Zn1) of 5 to 30 mass%, and a content (Fe1) of 45 to 85 mass%, The ferrite particles may have a Ni1 content of 6.25 to 27.5 mass%, a Zn1 content of 6.25 to 22.5 mass%, and an Fe1 content of 50 to 80 mass%, The ferrite particles may have a (Ni1) content of 7.5 to 25 mass %, a (Zn1) content of 7.5 to 25 mass %, and a (Fe1) content of 55 to 75 mass %.
[0034] In order to obtain ferrite particles having three divalent ions, the ferrite particles may further contain, for example, copper. The copper content in the ferrite particles can be measured by XRF analysis. The copper content in the ferrite particles of the embodiment is preferably 0.5 to 25 mass%, more preferably 1 to 20 mass%, and even more preferably 2.5 to 15 mass%, in terms of CuO content (Cu1) relative to 100 mass% of the ferrite particles, determined by XRF analysis of the ferrite particles.
[0035] In the ferrite particles of the embodiment, the upper and lower limit values of the above-mentioned content (Ni1), content (Zn1), content (Cu1) and content (Fe1) can be freely combined. In addition, the values of the content (Ni1), content (Zn1), content (Cu1) and content (Fe1) can also be freely combined.
[0036] As another example of the ferrite particles, cobalt may be contained instead of copper. The cobalt content in the ferrite particles can be measured by XRF analysis. The cobalt content in the ferrite particles of the embodiment is preferably 0.5 to 50 mass%, more preferably 1 to 25 mass%, and even more preferably 2.5 to 20 mass%, in terms of the content (Co1) in terms of Co2O3 relative to 100 mass% of the ferrite particles, determined by XRF analysis of the ferrite particles.
[0037] For the above-mentioned XRF analysis, an X-ray fluorescence analyzer (for example, Primus IV manufactured by Rigaku Corporation) can be used.
[0038] The content (Ni1) in terms of NiO refers to the value obtained from the amount of NiO obtained by converting the nickel content determined by XRF analysis of ferrite particles using a calibration curve in terms of NiO.
[0039] The content (Fe1) in terms of Fe2O3 refers to the value obtained from the amount of Fe2O3 converted by using a calibration curve in terms of Fe2O3 to convert the iron content determined by XRF analysis of ferrite particles.
[0040] The content (Cu1) calculated as CuO refers to the value obtained from the amount of CuO2 calculated by converting the copper content determined by XRF analysis of ferrite particles using a calibration curve calculated as CuO.
[0041] The content (Co1) calculated as Co2O3 refers to the value obtained from the amount of Co2O3 calculated by converting the cobalt content determined by XRF analysis of ferrite particles using a calibration curve calculated as Co2O3.
[0042] The ferrite particles of the embodiment contain ferrite. The ferrite particles may have various crystal structures such as a spinel structure or a garnet structure, but in this embodiment, the ferrite particles preferably have a spinel structure.
[0043] The median diameter D of the ferrite particles of the embodiment calculated by a laser diffraction / scattering method 50 The median diameter D is preferably 0.1 to 100 μm, more preferably 2.5 to 75 μm, and particularly preferably 5 to 50 μm. 50 It is preferable that the particle diameter is within the above range because the particles are well dispersed in the resin when kneaded with the resin composition.
[0044] The 10% diameter D of the ferrite particles of the embodiment calculated by a laser diffraction / scattering method 10 is preferably 0.1 μm or more, more preferably 0.25 μm or more, and particularly preferably 0.5 μm or more. 10 When the molecular weight is within the above range, the powder particles are prevented from absorbing moisture in the air and from being charged with static electricity, which improves the handling properties.
[0045] The 90% diameter D of the ferrite particles of the embodiment calculated by a laser diffraction / scattering method 90 is preferably 200 μm or less, more preferably 150 μm or less, and particularly preferably 100 μm or less. 90 When the content is within the above range, the surface of the molded article becomes smooth when the resin composition is molded, which is preferable.
[0046] The 10% diameter D 10 , median diameter D 50 , 90% diameter D 90 is calculated by a laser diffraction / scattering method. Specifically, a laser diffraction particle size distribution measuring device, for example, a laser diffraction particle size distribution analyzer HELOS (H3355)&RODOS, R3:0.5 / 0.9-175 μm (manufactured by Japan Laser Co., Ltd.), is used to measure the particle size distribution in a dry state under conditions of a dispersion pressure of 3 bar and a suction pressure of 90 mbar, and the 10% diameter D 10 , median diameter D 50 , 90% diameter D 90 can be sought.
[0047] The 10% diameter D of the ferrite particles of the embodiment calculated by a laser diffraction / scattering method10 , median diameter D 50 , and 90% diameter D 90 Therefore, the SPAN calculated by the following formula is preferably 0.7 to 2.0, more preferably 0.8 to 1.75, and particularly preferably 0.9 to 1.5. If the SPAN is within the above range, an increase in the kneading torque during kneading with the resin can be suppressed, and since there is a certain distribution in particle diameter, a combination of large and small particles can increase the filling rate of the filler in the resin, which is preferable. The SPAN is calculated by the following formula. SPAN=D 50 / (D 90 -D 10 )
[0048] The ferrite particles of the embodiment are D sa is preferably 1.0 μm or more, more preferably 1.5 μm or more, and even more preferably 2.0 μm or more. sa When the molecular weight ratio is equal to or more than the lower limit, an increase in viscosity is suppressed when the ferrite particles are kneaded with a resin, and the filling rate of the ferrite particles can be further improved, which is preferable.
[0049] Here, D sa This corresponds to a particle diameter calculated from the BET specific surface area of the ferrite particles, and is a value calculated from the specific surface area and specific gravity ρ of the ferrite particles according to the following formula. D sa =6 / (specific surface area x specific gravity ρ)
[0050] The specific surface area is measured using a specific surface area meter (e.g., BELSORP-mini, manufactured by Microtrack-Bell Corporation), and the surface area per 1 g of the sample measured from the amount of nitrogen gas adsorbed by the BET method (Brunauer-Emmett-Teller method) is defined as the specific surface area (m 2 / g)
[0051] The ferrite particles of the present invention have a particle diameter (D sa ) and median diameter D 50 Ratio of (D 50 / Dsa ) is preferably 3.6 or less, more preferably 3.5 or less, and even more preferably 3.4 or less. 50 / D sa When the ferrite particles have a smooth surface without irregularities, the oil absorption of each particle is suppressed, and the number of particles that can be dispersed in the same weight of resin can be increased, which is preferable when the ferrite particles have a smooth surface without irregularities, and the oil absorption of each particle is suppressed, and the number of particles that can be dispersed in the same weight of resin can be increased.
[0052] In the ferrite particles of the present invention, the number of fine particles adhering to the particle surface of the main particle is preferably 10 or less, more preferably 7.5 or less, and most preferably 5 or less. By having the number of fine particles adhering to the particle surface be within the above range, an increase in viscosity is suppressed when kneaded with a resin, and the packing rate of the ferrite particles can be further improved, which is preferable.
[0053] Here, the fine particles are defined as particles with a median diameter D 50 The particle size of the fine particles is 1 / 20 or less of the diameter of the ferrite particles. The particle size of the fine particles is determined by measuring the maximum length between two points on the outline of the primary particle in an SEM image, and taking the average value as the primary particle size of the ferrite particles, and taking the median diameter D 50 The primary particle diameter of the fine particles was defined as 1 / 20 or less of the median diameter D 50 The number of the fine particles attached to each particle (having a primary particle diameter larger than 1 / 20 of the particle diameter) was counted. The number of fine particles is the average value measured for 50 random particles observed in an SEM image (magnification 2000 times).
[0054] The main particle is the median diameter D of the entire ferrite particle. 50 This refers to particles whose particle size is not 1 / 20 or less of the particle size of the main particle. In other words, particles that do not fit the above definition of fine particles are considered main particles.
[0055] The ferrite particles of the embodiment are ferrite particles having a controlled particle shape, i.e., not amorphous, and more preferably have a polyhedral shape. The shape of the ferrite particles can be confirmed by a scanning electron microscope (SEM).
[0056] The aggregate of ferrite particles (ferrite powder) may contain ferrite particles having a shape other than a polyhedral shape in any state. The content of the polyhedral ferrite particles is preferably 80% or more by weight or number based on the total amount of the ferrite powder, more preferably 90% or more, and even more preferably 95% or more.
[0057] <Method of manufacturing ferrite particles> The method for producing ferrite particles according to the embodiment includes calcining a metal compound and an iron compound in the presence of a molybdate compound. More specifically, the method for producing ferrite particles according to the embodiment may include mixing the metal compound, the iron compound, and the molybdate compound to form a mixture, and calcining the mixture.
[0058] By calcining a metal compound and an iron compound in the presence of a molybdate compound, the reaction efficiency of ferrite particle production can be improved compared to the case where a molybdenum compound is not used, and therefore high-quality ferrite particles can be efficiently produced, and furthermore, ferrite particles with fewer bonded particles (necking particles) can be easily produced.
[0059] The molybdate used in the production method of this embodiment has a 90% diameter D 90 It is preferable that the particle size of the molybdate is in the range of 1 to 100 μm. By using a molybdate having a particle size in the above range, it is possible to obtain ferrite particles having a smooth particle shape and / or to make the number of fine particles relative to the number of main particles equal to or less than a desired number, which is preferable. Furthermore, 10% diameter D 10 It is particularly preferable that the particle size is in the range of 0.1 to 10 μm, since the particle size distribution of the whole particles becomes uniform.
[0060] As the metal compound, two or more metal compounds containing any element selected from Ni, Mn, Cu, Zn, Mg, Ca, and Co can be used. Examples of the metal compound include nickel compounds, manganese compounds, copper compounds, zinc compounds, magnesium compounds, calcium compounds, and cobalt compounds.
[0061] The combination of metal compounds is not particularly limited, but by adding a certain proportion of a paramagnetic substance, the magnetism of the Td site is appropriately reduced and the magnetism derived from the interaction of the Td-Oh site is enhanced. In order to do so, it is preferable to add, for example, a magnesium compound or a zinc compound, and it is more preferable to add a zinc compound.
[0062] According to the method for producing ferrite particles of the embodiment, the ferrite particles of the embodiment described above can be easily produced.
[0063] A preferred method for producing ferrite particles includes a step of mixing two or more metal compounds containing any one of elements selected from Ni, Mn, Cu, Zn, Mg, Ca, and Co, an iron compound, and a molybdate compound to obtain a mixture (mixing step), and a step of firing the mixture (firing step). Hereinafter, a case where a nickel compound and a zinc compound are used as an example of the metal compounds will be described.
[0064] [Mixing process] The mixing step is a step of mixing a nickel compound, a zinc compound, an iron compound, and a molybdate compound to obtain a mixture. The contents of the mixture will be described below.
[0065] (Nickel compounds) The type of the nickel compound is not particularly limited. For example, the nickel compound may be nickel hydroxide, nickel oxide, nickel carbonate, nickel chloride, nickel nitrate, nickel sulfate, nickel acetate, etc., of which nickel hydroxide, nickel oxide, and nickel carbonate are preferred, and nickel hydroxide or nickel oxide is more preferred from the viewpoint of reactivity and the absence of harmful gas generation.
[0066] Since the shape of the ferrite particles after sintering hardly reflects the shape of the raw material nickel compound, for example, spherical, amorphous, large aspect structures (wires, fibers, ribbons, tubes, etc.), sheets, etc. can be suitably used as the nickel compound.
[0067] (Zinc compounds) The type of the zinc compound is not particularly limited. For example, examples of the zinc compound include zinc hydroxide, zinc oxide, zinc carbonate, zinc acetate, zinc chloride, zinc nitrate, zinc sulfate, etc., and zinc hydroxide, zinc oxide, and zinc carbonate are preferred, and zinc hydroxide or zinc oxide is preferred from the viewpoint of reactivity and the absence of harmful gas generation.
[0068] Since the shape of the ferrite particles after firing hardly reflects the shape of the raw material zinc compound, for example, spherical, amorphous, large aspect structures (wires, fibers, ribbons, tubes, etc.), sheets, etc. can be suitably used as the nickel compound.
[0069] (Iron Compounds) The type of iron compound is not particularly limited, and known compounds can be used. Specific examples of these include iron oxide (II) (FeO), so-called wustite, black iron oxide (II,III) (Fe3O4), and reddish-brown iron oxide (III) (Fe2O3). Examples of iron oxide (III) include α-Fe2O3, β-Fe2O3, γ-Fe2O3, and ε-Fe2O3. Examples of iron oxyhydroxide include α-iron oxyhydroxide, β-iron oxyhydroxide, γ-iron oxyhydroxide, δ-iron oxyhydroxide, and the like. Examples of iron hydroxide include iron hydroxide (II) (Fe(OH)2) and iron hydroxide (III) (Fe(OH)3). As the iron oxide, iron oxide (III) (Fe2O3) is preferred.
[0070] The shape of the iron compound is not particularly limited, but for example, a spherical, rod-like or plate-like shape can be suitably used.
[0071] (Molybdate Compounds) The molybdate compound is MoO4 2- , Mo2O7 2- , Mo3O 10 2- , Mo4O 13 2- , Mo5O 16 2- , Mo6O 19 2- , Mo7O 24 6- , Mo8O 26 4- The molybdenum oxoanion may be, but is not limited to, a salt compound of the molybdenum oxoanion such as those mentioned above. The molybdenum oxoanion may be an alkali metal salt, an alkaline earth metal salt, or an ammonium salt.
[0072] The molybdate compound is preferably an alkali metal salt of a molybdenum oxoanion, more preferably lithium molybdate, sodium molybdate or potassium molybdate, even more preferably sodium molybdate or potassium molybdate, and particularly preferably sodium molybdate.
[0073] In the method for producing ferrite particles of this embodiment, the molybdate compound may be a hydrate.
[0074] By using a molybdate compound, the formation of metal molybdate salts is suppressed compared to the case of using a molybdenum compound. In addition, by using a molybdate compound prepared in advance, the reactivity of the molybdate compound can be controlled. As a result, the particle growth and surface roughness of the obtained ferrite particles can be easily adjusted to the desired level, which is preferable.
[0075] In the case of ferrite particles having three divalent ions, a copper compound or a cobalt compound can be further combined as a raw material. The metal compound to be combined is not limited to a copper compound or a cobalt compound, but may be a manganese compound, a magnesium compound, or a calcium compound. Hereinafter, a detailed description will be given of a case where a copper compound or a cobalt compound is used as an example.
[0076] (copper compound) The type of the copper compound is not particularly limited. For example, the copper compound may be copper hydroxide, copper oxide, copper carbonate, copper acetate, copper chloride, copper nitrate, copper sulfate, etc., and copper hydroxide, copper oxide, and copper carbonate are preferred, and copper hydroxide and copper oxide are preferred from the viewpoint of reactivity and the absence of harmful gases.
[0077] (Cobalt compounds) The type of the cobalt compound is not particularly limited. For example, the cobalt compound may be cobalt oxide, cobalt carbonate, cobalt acetate, cobalt chloride, cobalt bromide, cobalt nitrate, cobalt sulfate, etc., and preferably cobalt oxide or cobalt carbonate, more preferably cobalt oxide, from the viewpoint of reactivity and the absence of harmful gas generation.
[0078] In the embodiment of the method for producing ferrite particles, a preferred combination of raw materials is a spinel structure of the ferrite particles. x Zinc 1-x When expressed as Fe2O4, examples of the materials that can be used include nickel oxide, zinc oxide, iron (III) oxide, and sodium molybdate.
[0079] In the embodiment of the method for producing ferrite particles, a preferable combination of raw materials is a combination of Ni x Cu y Zinc 1-x-y When expressed as Fe2O4, examples of the materials that can be used include nickel oxide, zinc oxide, copper oxide, iron (III) oxide, and sodium molybdate.
[0080] In the method for producing ferrite particles according to the embodiment, a preferable combination of raw materials is a combination of raw materials in which the spinel structure of the ferrite particles is Co. x Zinc y Ni 1-x-y When expressed as Fe2O4, examples of materials that can be used include cobalt oxide, zinc oxide, nickel oxide, iron (III) oxide, and sodium molybdate.
[0081] (Other metal compounds) Other metal compounds may be used during calcination if desired. The other metal compounds are not particularly limited, but preferably include at least one selected from the group consisting of Group II metal compounds and Group III metal compounds.
[0082] Examples of the Group II metal compound include calcium compounds, strontium compounds, and barium compounds.
[0083] Examples of the Group III metal compound include a scandium compound, an yttrium compound, a lanthanum compound, and a cerium compound.
[0084] The above-mentioned other metal compounds refer to oxides, hydroxides, carbonates, and chlorides of metal elements. For example, yttrium compounds include yttrium oxide (Y2O3), yttrium hydroxide, and yttrium carbonate. Of these, the other metal compounds are preferably oxides of metal elements. These other metal compounds include isomers.
[0085] Among these, the metal compounds of the third periodic elements, the metal compounds of the fourth periodic elements, the metal compounds of the fifth periodic elements, and the metal compounds of the sixth periodic elements are preferred, the metal compounds of the fourth periodic elements and the metal compounds of the fifth periodic elements are more preferred, and the metal compounds of the fifth periodic elements are even more preferred. Specifically, it is preferred to use calcium compounds, yttrium compounds, and lanthanum compounds, it is more preferred to use calcium compounds and yttrium compounds, and it is particularly preferred to use yttrium compounds.
[0086] The other metal compound is preferably used in a proportion of, for example, 0 to 1.2 mass % (for example, 0 to 1 mol %) relative to the total amount of the above metal compounds used in the mixing step.
[0087] In the method for producing ferrite particles of this embodiment, the amounts of the nickel compound, zinc compound, iron compound, and molybdate compound used are not particularly limited, but in the raw material, for example in the mixture, the ratio of the total mass of the nickel compound, zinc compound, and iron compound to the mass of the molybdate compound may be 2 to 100, 2.5 to 75, or 5 to 50.
[0088] In the method for producing ferrite particles of this embodiment, when a copper compound is further blended, the amounts of the nickel compound, copper compound, zinc compound, iron compound and molybdate compound used are not particularly limited, but in the raw material, for example in the mixture, the ratio of the total mass of the nickel compound, copper compound, zinc compound and iron compound to the mass of the molybdate compound may be 2 to 100, 2.5 to 75, or 5 to 50.
[0089] In the method for producing ferrite particles of this embodiment, when a cobalt compound is further blended instead of a copper compound, the amounts of the nickel compound, cobalt compound, zinc compound, iron compound and molybdate compound used are not particularly limited, but in the raw material, for example in the mixture, the ratio of the total mass of the nickel compound, cobalt compound, zinc compound and iron compound to the mass of the molybdate compound may be 1 to 100, 2.0 to 75, or 2.5 to 50.
[0090] In the method for producing ferrite particles of the present embodiment, the molar ratio of nickel to iron (Ni / Fe) in the raw material, for example, in the mixture, may be 0.1 to 0.6, or 0.2 to 0.5.
[0091] [Raw material preparation process] The molybdate compound used in the method for producing ferrite particles of the present embodiment has a 90% diameter D 90 is preferably 1 to 100 μm, and more preferably 10 to 100 μm. By being within the above range, it is possible to easily obtain ferrite particles having a smooth particle shape and / or a number of fine particles adhering to the main particles within a desired range, which is preferable. In addition, the 10% diameter D 10 is preferably 0.1 to 10 μm, and particularly preferably 0.5 to 10 μm. 90 and 10% diameter D 10 However, it is particularly preferable that any of the above-mentioned ranges is satisfied, since this increases the efficiency with which the molybdate is mixed into the powder of other raw materials in the mixing step.
[0092] The molybdate compound has a desired 90% diameter D 90 It is preferable to crush and / or sieve the mixture so that the mixture is in the range of 100 to 1500 nm. The crushing method is not particularly limited, but may be a ball mill or a bottle blender. As the sieving method, it is preferable to use a sieve with an opening of 106 μm.
[0093] The amount of the molybdate compound is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 20% by mass or less, based on the total amount of other metal compounds. The amount of the molybdate compound within the above range is preferable because it reduces the burden of removing the molybdate by washing after firing. The minimum amount of the molybdate compound is preferably 1% by mass or more.
[0094] The obtained molybdate compound is preferably mixed with other raw materials, for example, a nickel compound, a zinc compound, and an iron compound, to form a mixture. The mixing method is not particularly limited, but may be a simple mixing method using a manual technique such as shaking or kneading in a bag, mechanical mixing using a grinder, mixing using a mortar, mixing in a dry state, or mixing in a wet state.
[0095] [Firing process] The calcination step is a step of calcining the mixture. As described above, the production method of the present embodiment includes calcining a nickel compound, a zinc compound, and an iron compound in the presence of a molybdate compound. In addition, when the mixture containing the nickel compound, the zinc compound, the iron compound, and the copper compound or the cobalt compound is obtained in the mixing step, the method may include calcining the nickel compound, the zinc compound, the iron compound, and the copper compound or the cobalt compound in the presence of a molybdate compound. The ferrite particles according to the embodiment are obtained by firing the mixture. As described above, this manufacturing method is called the flux method.
[0096] The flux method has the advantages of being able to grow crystals at temperatures much lower than the melting point, being able to precisely control the crystal structure, and being able to form idiomorphic crystals.
[0097] It is speculated that the following reaction mechanism is involved in the production of ferrite particles using a molybdate compound as a flux. For example, when a nickel compound, a zinc compound, and an iron compound are sintered in the presence of a molybdate compound, ferrite crystals are obtained by crystal growth. In this case, by using a molybdate compound, the molybdate compound melted at high temperatures and various raw materials are dissolved in solid solution, and mass transfer occurs at a temperature lower than the melting point of the various raw materials, and the reaction proceeds. In addition, since the reaction is not a solid-phase reaction but a reaction via the liquid phase of the molybdate compound that appears on the particle surface, it is speculated that ferrite particles with a smooth particle shape without unevenness or step structure and / or a small number of fine particles attached to the main particle can be obtained.
[0098] The firing method is not particularly limited, and can be performed by a known and conventional method. The state of the nickel compound, zinc compound, iron compound, and molybdate compound during firing is not particularly limited, and the molybdate compound may be present in the same space so that it can act on the nickel compound, zinc compound, and iron compound. Specifically, it may be a simple mix of mixing the powder of the molybdate compound, the powder of the nickel compound, the powder of the zinc compound, and the powder of the iron compound, a mechanical mix using a grinder, or a mix using a mortar, and may be mixed in a dry state or a wet state.
[0099] In addition, when the mixture containing the copper compound and / or cobalt compound is fired, the state of the nickel compound, zinc compound, iron compound, copper compound and / or cobalt compound, and molybdate compound is not particularly limited, and it is sufficient that the molybdate compound is present in the same space where it can act on the nickel compound, zinc compound, iron compound, copper compound and / or cobalt compound. Specifically, it may be a simple mixing method in which a powder of a molybdate compound, a powder of a nickel compound, a powder of a zinc compound, a powder of an iron compound, and a powder of a copper compound and / or cobalt compound are mixed together, a mechanical mixing method using a grinder, or a mixing method using a mortar, or it may be a mixing method in a dry state or a wet state.
[0100] The firing temperature condition is not particularly limited, and is appropriately determined in consideration of the particle size of the target ferrite particles, the formation of a molybdate compound in the ferrite particles, the shape of the ferrite particles, etc. The firing temperature is preferably 950°C or higher, more preferably 1000°C or higher, even more preferably 1050°C or higher, and particularly preferably 1100°C or higher.
[0101] When the firing temperature is equal to or higher than the lower limit, mass transfer is promoted, and ferrite particles having a small number of fine particles adhering to the main particles, a narrow particle size distribution, and a small SPAN value tend to be obtained.
[0102] Generally, in order to control the shape of ferrite particles obtained after sintering or to improve their magnetic properties, sintering at high temperatures of over 1500°C is necessary. However, there are significant challenges to be overcome in terms of the burden on the sintering furnace and energy costs in order to utilize this method industrially.
[0103] According to one embodiment of the present invention, even under conditions where the maximum sintering temperature for sintering a nickel compound and a zinc compound is 1500°C or lower, ferrite particles can be formed efficiently at low cost, which contributes to reducing energy costs and environmental loads.
[0104] Furthermore, according to the method for producing ferrite particles of the embodiment, idiomorphous ferrite particles can be formed regardless of the shape of the precursor even if the firing temperature is 1500° C. or lower, which is a temperature lower than the melting point of iron oxide. From this viewpoint, the firing temperature is preferably 1500° C. or lower, more preferably 1400° C. or lower, and particularly preferably 1300° C. or lower.
[0105] The range of the calcination temperature at which the nickel compound and the iron compound are calcined in the calcination step may be, for example, 800 to 1500°C, 900 to 1500°C, 950 to 1400°C, or 1000 to 1300°C.
[0106] From the viewpoint of production efficiency, the temperature rise rate may be 20 to 600° C. / h, 40 to 500° C. / h, or 80 to 400° C. / h.
[0107] Regarding the firing time, the time required to raise the temperature to a predetermined firing temperature is preferably within the range of 15 minutes to 10 hours. The holding time at the firing temperature can be 5 minutes or more, and is preferably within the range of 5 minutes to 1000 hours, and more preferably within the range of 1 to 30 hours. In order to efficiently form ferrite particles, it is more preferable to hold the firing temperature for 2 hours or more, and particularly preferably to hold the firing temperature for 2 to 24 hours.
[0108] As an example, by selecting conditions of a firing temperature of 800 to 1300° C. and a firing temperature holding time of 2 to 24 hours, ferrite particles of the embodiment containing molybdenum can be easily obtained.
[0109] The firing atmosphere is not particularly limited as long as the effects of the present invention can be obtained. For example, an oxygen-containing atmosphere such as air or oxygen, or an inert atmosphere such as nitrogen, argon, or carbon dioxide is preferable, and an air atmosphere is more preferable in terms of cost.
[0110] The calcination device is not necessarily limited, and a so-called calcination furnace can be used.
[0111] [Cooling process] The method for producing ferrite particles may include a cooling step, which is a step of cooling the ferrite particles that have undergone crystal growth in the firing step.
[0112] The cooling rate is not particularly limited, but is preferably 1 to 1000°C / hour, more preferably 5 to 500°C / hour, and even more preferably 50 to 100°C / hour. A cooling rate of 1°C / hour or more is preferable because the manufacturing time can be shortened. On the other hand, a cooling rate of 1000°C / hour or less is preferable because the firing container is less likely to crack due to heat shock and can be used for a long time.
[0113] The cooling method is not particularly limited, and may be natural cooling or a cooling device may be used.
[0114] [Molybdate removal process] The method for producing ferrite particles according to the present embodiment may further include, after the firing step, a molybdate removal step of removing at least a portion of the molybdate, as necessary.
[0115] The method includes a washing process.
[0116] Molybdate may adhere to the surface of the ferrite particles. As a means other than the sublimation, the molybdate may be removed by washing with water, warm water, hot water, dilute hydrochloric acid, aqueous sodium hydroxide solution, or the like.
[0117] In this case, the molybdenum content in the ferrite particles can be controlled by appropriately changing the concentration and amount of water, warm water, hot water, dilute hydrochloric acid, or sodium hydroxide aqueous solution used, as well as the cleaning area and cleaning time.
[0118] [Crushing process] In the sintered product obtained through the sintering step, the ferrite particles may aggregate and may not satisfy the suitable particle size range for the intended application. Therefore, the ferrite particles may be pulverized as necessary to satisfy the suitable particle size range. The method for pulverizing the fired product is not particularly limited, and any conventionally known pulverizing method such as a ball mill, a jaw crusher, a jet mill, a disk mill, a spectromill, a grinder, or a mixer mill can be used.
[0119] [Classification process] The sintered product containing ferrite particles obtained by the sintering step may be appropriately classified to adjust the range of particle sizes. "Classification" refers to an operation of classifying particles into groups according to their sizes.
[0120] The classification may be either a wet type or a dry type, but from the viewpoint of productivity, a dry type classification is preferred. Dry classification includes classification using a sieve as well as wind classification, which classifies based on the difference between centrifugal force and fluid drag. From the viewpoint of classification accuracy, wind classification is preferred, and can be carried out using a classifier such as an air current classifier that utilizes the Coanda effect, a swirling air current classifier, a forced vortex centrifugal classifier, or a semi-free vortex centrifugal classifier.
[0121] The above-mentioned pulverization step and classification step can be carried out at any stage required. Depending on whether or not pulverization or classification is performed and the selection of the conditions therefor, for example, the average particle size of the obtained ferrite particles can be adjusted.
[0122] In addition, according to the method for producing ferrite particles of this embodiment, it is possible to easily produce ferrite particles with little or no agglomeration, and therefore it has the excellent advantage that ferrite particles having the desired excellent properties can be produced with high productivity without performing the above-mentioned crushing and classification processes.
[0123] The ferrite particles of the embodiment, or the ferrite particles obtained by the manufacturing method of the embodiment, are less aggregated or are not aggregated at all, so that they are more likely to exhibit their inherent properties and are more easily handled. In addition, when dispersed in a dispersion medium for use, they are preferred from the viewpoint of having better dispersibility.
[0124] <Ferrite particle-containing resin composition> The ferrite particles of the present embodiment can be suitably used in a resin composition. Specifically, since the ferrite particles of the present embodiment have excellent particle properties, when used in a resin composition, the ferrite particles not only exhibit excellent magnetic properties, but also have both high packing of the ferrite particles and excellent handling properties.
[0125] The content of the ferrite particles in the resin composition is preferably 75 wt% or more, and more preferably 80 wt% or more, calculated as solid content. Compared with conventional ferrite particles, the ferrite particles of the present embodiment have a smooth particle shape and / or the number of fine particles relative to the main particles is a specific number or less, so that deterioration of handleability can be suppressed when the filling rate is increased. As a result, the filling rate in the resin can be increased compared with conventional ferrite particles, and therefore a resin composition excellent in the imaginary component μ” of complex permeability and other magnetic properties can be obtained compared with conventional ferrite particle-containing resin compositions.
[0126] The resin used in the resin composition is not particularly limited, and various thermoplastic resins and thermosetting resins can be used.
[0127] The thermoplastic resin is not particularly limited, but examples thereof include polyester resin, polyarylene sulfide resin, polyamide resin, polyimide resin, polyetherimide resin, polycarbonate resin, polyphenylene ether resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyetherketone resin, polyarylene resin, syndiotactic polystyrene resin, polyethylene resin, polypropylene resin, polytetrafluoroethylene resin, polydifluoroethylene resin, polystyrene resin, acrylonitrile-butadiene-styrene (ABS) resin, phenol resin, urethane resin, liquid crystal polymer, styrene-based elastomer, vinyl chloride-based elastomer, olefin-based elastomer, polyester-based elastomer, polyamide-based elastomer, polyurethane-based elastomer, etc. These resins may be used alone or in combination of two or more. Among these, thermoplastic elastomers such as styrene-based elastomers, vinyl chloride-based elastomers, olefin-based elastomers, polyester-based elastomers, polyamide-based elastomers, and polyurethane-based elastomers are preferred, and styrene-based elastomers are particularly preferred from the viewpoints of heat resistance and flexibility.
[0128] The thermosetting resin is not particularly limited, but examples thereof include epoxy resin, phenol resin, oxetane resin, (meth)acrylate resin, unsaturated polyester resin, diallyl phthalate resin, maleimide resin, silicone resin, etc. These resins may be used alone or in combination of two or more. Among these, silicone resin is particularly preferred because of its good mold release.
[0129] The ferrite particles of the present embodiment can be highly packed while maintaining ease of handling, regardless of the type of resin, but are particularly preferred in combination with a thermosetting resin, in order to achieve the above-mentioned effects.
[0130] The resin composition only needs to contain ferrite particles and a resin, and may further contain components other than these (other components).
[0131] Examples of other components include various colorants such as pigments and dyes; various fluorescent materials; various phosphorescent materials; various phosphorescent materials; solvents; infrared absorbing materials; ultraviolet absorbers; dispersants; surfactants; polymerization initiators; polymerization accelerators; crosslinking agents; polymerization inhibitors; sensitizers; plasticizers; slip agents (leveling agents); penetration accelerators; wetting agents (moisturizing agents); antistatic agents; fixing agents; preservatives; antifungal agents; antioxidants; chelating agents; pH adjusters; thickeners; fillers such as alumina, silica, titanium oxide, magnesium oxide, antimony oxide, calcium oxide, zinc oxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, potassium titanate, glass fibers, carbon fibers, gypsum fibers, metal fibers, metal particles, graphite, talc, clay, mica, wollastonite, xonotlite, hydrotalcite, and zeolite; anti-aggregating agents; defoaming agents; and foaming agents.
[0132] The content of other components is not particularly limited as long as it does not deteriorate the magnetic properties or handling properties of the resulting resin composition, but it is preferably, for example, 0.1 to 10 wt % based on the total solid content in the resin composition.
[0133] The resin composition can be produced, for example, by mixing the ferrite powder of the present invention with a resin material. The mixing of the ferrite powder with the resin material can be suitably carried out using a mixing device (kneading device) such as a planetary mixer, a twin-screw mixer, a kneader, a Banbury mixer, or an oven roll, or a single-screw extruder or a twin-screw extruder.
[0134] Since the resin composition contains ferrite particles having a smooth particle shape and / or a specific number or less of fine particles relative to main particles, the resin composition has excellent handleability even when the ferrite particles are contained at a content rate similar to that of conventional ferrite particles.
[0135] The handleability can be evaluated, for example, by the kneading torque value. A resin composition obtained by mixing 40 vol% of the thermoplastic resin and 60 vol% of the ferrite particles is kneaded at 240°C and 33 rpm using a test kneading device, Labo Plastomill (registered trademark, Toyo Seiki Seisakusho Co., Ltd.), equipped with a small segment mixer KF15V, and the kneading torque value is recorded. If the average torque value is 40 N·m or less, the handleability can be determined to be good. As another evaluation method, a THINKY MIXER (ARV-200, manufactured by THINKY CORPORATION) can be used to check whether kneading is possible when the ferrite particle content is in the range of 75 wt % to 85 wt %.
[0136] The resin composition has excellent handleability and can be easily molded, making it possible to obtain a molded article having excellent magnetic properties.
[0137] As a method for producing a molded body, various molding methods can be used, for example, injection molding (insert molding, multicolor molding, sandwich molding, injection molding, etc.), compression molding, extrusion molding, inflation molding, T-die film molding, laminate molding, blow molding, hollow molding, compression molding, calendar molding, various coating methods, photolithography, three-dimensional additive manufacturing, etc.
[0138] <Application> The ferrite particle-containing resin composition of the present invention has excellent magnetic properties and can therefore be suitably used for RFID sheets, noise suppression sheets, etc. In particular, since it is possible to produce a resin composition with a high filling rate and a large imaginary component μ″ of complex magnetic permeability compared to conventional ferrite particles, it can be suitably used for noise suppression sheets. EXAMPLES
[0139] <Production of sodium molybdate> [Production Example 1] 168.14 g of disodium molybdate (VI) dihydrate (Na2MoO4·2H2O) and 100.00 g of molybdenum oxide (MoO3) were mixed to obtain a mixture. The resulting mixture was placed in a crucible and fired in a muffle furnace at 700°C for 5 hours. The temperature was increased at a rate of 3°C / min. After the temperature was lowered to room temperature, the crucible was removed to obtain white crystals. The crystals were pulverized using a bottle blender (Waring Corporation; 7011HBC) and passed through a sieve with 106μm openings to obtain the powder of Production Example 1. When this powder was subjected to XRD measurement, diffraction peaks originating from Na2Mo2O7 were confirmed, confirming the synthesis of Na2Mo2O7. 10 is 1.3 μm, and D 90 was confirmed to be 65 μm.
[0140] [Production Example 2] 60.00 g of disodium molybdate (VI) dihydrate (Na2MoO4·2H2O) and 71.42 g of molybdenum oxide (MoO3) were mixed to obtain a mixture. The resulting mixture was placed in a crucible and fired in a muffle furnace at 750°C for 5 hours. The temperature was increased at a rate of 3°C / min. After the temperature was lowered to room temperature, the crucible was removed to obtain white crystals. The crystals were pulverized using a bottle blender (Waring Corporation; 7011HBC) and passed through a sieve with 106μm openings to obtain the powder of Production Example 2. XRD measurement of this powder revealed that Na2Mo3O 10 The diffraction peaks due to Na2Mo3O 10 The synthesis of D was confirmed. 10 is 5.0 μm, and D 90 was confirmed to be 80 μm.
[0141] [Production Example 3] After calcination in the same manner as in Production Example 1, white crystals were obtained, and then pulverized with a hammer until they were powdery, to obtain the powder of Production Example 3. The particle size distribution was then measured, and it was found that D 10 is 15 μm, and D 90 was confirmed to be 250 μm.
[0142] [Example 1] 66.80g of iron oxide (Kanto Chemical Co., Ltd.), 9.37g of nickel oxide (Kanto Chemical Co., Ltd.), 23.83g of zinc oxide (Kanto Chemical Co., Ltd.), 10.00g of sodium molybdate (Na2Mo2O7) produced in the above Production Example 1, and 300g of 5mmφ zirconia beads were charged into a 250ml zirconia pot, and mixed and ground for 30 minutes at 150 rpm using a planetary ball mill (Sansho Industry Co., Ltd.) to obtain a mixture. The resulting mixture was placed in a crucible and fired at 1100°C for 5 hours in a ceramic electric furnace. The temperature was raised at 5°C / min. After the temperature was lowered, the crucible was removed and a black powder was obtained. The powder was then transferred to a 1 L plastic bottle, 250 ml of hot water was added, and the mixture was shaken for 10 minutes using a shaker (manufactured by AZONE Co., Ltd.), after which the supernatant was removed. This procedure was repeated four times. The obtained precipitate was dried at 120° C. for 24 hours to obtain 99.8 g of a black powder.
[0143] [Example 2] 99.3 g of black powder was obtained by the same method as in Example 1, except that the amount of each raw material was changed to 66.80 g of iron oxide (manufactured by Kanto Chemical Co., Ltd.), 13.50 g of nickel oxide (manufactured by Kanto Chemical Co., Ltd.), and 20.25 g of zinc oxide (manufactured by Kanto Chemical Co., Ltd.).
[0144] [Example 3] 67.17g of iron oxide (Kanto Chemical Co., Ltd.), 15.71g of nickel oxide (Kanto Chemical Co., Ltd.), 17.12g of zinc oxide (Kanto Chemical Co., Ltd.), 3.00g of sodium molybdate (Na2Mo2O7) produced in the above Production Example 1, and 300g of 5mmφ zirconia beads were charged into a 250ml zirconia pot, and mixed and ground for 30 minutes at 150 rpm using a planetary ball mill (Sansho Industry Co., Ltd.) to obtain a mixture. The resulting mixture was placed in a crucible and fired at 1100°C for 5 hours in a ceramic electric furnace. The temperature was raised at 5°C / min. After the temperature was lowered, the crucible was removed and a black powder was obtained. The powder was then transferred to a 1 L plastic bottle, 250 ml of hot water was added, and the mixture was shaken for 10 minutes using a shaker (manufactured by AZONE Co., Ltd.), after which the supernatant was removed. This procedure was repeated four times. The obtained precipitate was dried at 120° C. for 24 hours to obtain 99.0 g of a black powder.
[0145] [Example 4] A black powder (99.5 g) was obtained in the same manner as in Example 3, except that the amount of sodium molybdate (Na2Mo2O7) added was 10.00 g.
[0146] [Example 5] A black powder (99.8 g) was obtained in the same manner as in Example 3, except that the amount of sodium molybdate (Na2Mo2O7) added was 12.00 g and the firing time was 10 hours.
[0147] [Example 6] Sodium molybdate (Na2Mo3O 10 99.0 g of black powder was obtained in the same manner as in Example 3, except that 10.00 g of 1,300° C. was used, the firing temperature was 1,300° C., and the firing time was 24 hours.
[0148] [Example 7] 99.7 g of black powder was obtained by the same method as in Example 1, except that the amount of each raw material was changed to 67.36 g of iron oxide (manufactured by Kanto Chemical Co., Ltd.), 18.90 g of nickel oxide (manufactured by Kanto Chemical Co., Ltd.), and 13.74 g of zinc oxide (manufactured by Kanto Chemical Co., Ltd.).
[0149] [Example 8] 99.4 g of black powder was obtained by the same method as in Example 1, except that the amounts of each raw material were changed to 67.55 g of iron oxide (manufactured by Kanto Chemical Co., Ltd.), 22.11 g of nickel oxide (manufactured by Kanto Chemical Co., Ltd.), and 10.34 g of zinc oxide (manufactured by Kanto Chemical Co., Ltd.).
[0150] [Example 9] 99.4 g of black powder was obtained by the same method as in Example 1, except that the amounts of each raw material were changed to 67.02 g of iron oxide (manufactured by Kanto Chemical Co., Ltd.), 12.51 g of nickel oxide (manufactured by Kanto Chemical Co., Ltd.), 17.11 g of zinc oxide (manufactured by Kanto Chemical Co., Ltd.), and 3.34 g of copper oxide (manufactured by Kanto Chemical Co., Ltd.).
[0151] [Example 10] 99.1 g of black powder was obtained by the same method as in Example 1, except that the amounts of each raw material were changed to 59.23 g of iron oxide (manufactured by Kanto Chemical Co., Ltd.), 13.85 g of nickel oxide (manufactured by Kanto Chemical Co., Ltd.), 9.06 g of zinc oxide (manufactured by Kanto Chemical Co., Ltd.), and 17.86 g of cobalt oxide (manufactured by Kanto Chemical Co., Ltd.).
[0152] [Example 11] 99.0 g of black powder was obtained by the same method as in Example 1, except that the amounts of each raw material were changed to 59.08 g of iron oxide (manufactured by Kanto Chemical Co., Ltd.), 11.05 g of nickel oxide (manufactured by Kanto Chemical Co., Ltd.), 12.05 g of zinc oxide (manufactured by Kanto Chemical Co., Ltd.), and 17.82 g of cobalt oxide (manufactured by Kanto Chemical Co., Ltd.).
[0153] [Comparative Example 1] A commercially available magnetic filler BSN-714 (manufactured by Toda Kogyo Co., Ltd.) was used.
[0154] [Comparative Example 2] A commercially available magnetic filler BSN-828 (manufactured by Toda Kogyo Co., Ltd.) was used.
[0155] [Comparative Example 3] A black powder (99.3 g) was obtained in the same manner as in Example 3, except that the sodium molybdate (Na2Mo2O7) produced in Production Example 3 was used.
[0156] [Comparative Example 4] A reddish black powder (99.9 g) was obtained in the same manner as in Example 3, except that no molybdate was used.
[0157] Evaluation The ferrite particles obtained in Examples 1-11 and Comparative Examples 1-3 were evaluated as follows.
[0158] [Crystal structure analysis: XRD (X-ray diffraction) method] The sample powder was filled into a measurement sample holder with a depth of 0.5 mm, which was then set into a wide-angle X-ray diffraction (XRD) device (Ultima IV, manufactured by Rigaku Corporation) and measurements were performed under the following conditions: Cu / Kα radiation, 40 kV / 40 mA, scan speed 2° / min, and scan range 10 to 70°.
[0159] [Specific surface area measurement] The specific surface area of the ferrite particles was measured using a fully automatic specific surface area measuring device (Macsorb Model HM-1210, manufactured by Mountec Co., Ltd.), and the surface area per 1 g of sample measured from the amount of nitrogen gas adsorbed by the BET method was defined as the specific surface area (m 2 / g).
[0160] [Particle size distribution measurement] The particle size distribution of the sample powder was measured in a dry state using a laser diffraction type dry particle size distribution analyzer (HELOS (H3355) & RODOS, manufactured by Japan Laser Co., Ltd.) under the conditions of a dispersion pressure of 3 bar and a suction pressure of 90 mbar. The particle size at the point where the distribution curve of the volume cumulative percentage intersects with the horizontal axis of 50% was defined as D. 50 was requested as follows.
[0161] [Evaluation of fine particles] The ferrite particles were photographed with a scanning electron microscope (SEM), and the maximum length between two points on the outline of the primary particle was measured from the SEM image. The average value was taken as the primary particle diameter of the ferrite particles, and the median diameter D 50 The primary particle diameter of the fine particles was defined as 1 / 20 or less of the median diameter D 50 The number of the fine particles attached to each particle (having a primary particle diameter larger than 1 / 20 of the particle diameter) was counted. The number of fine particles was calculated by measuring and averaging 50 random particles observed in an SEM image (magnification 2000 times).
[0162] [XRF (X-ray fluorescence) analysis] Using an X-ray fluorescence analyzer (Rigaku Corporation, Primus IV), approximately 70 mg of the sample powder was placed on filter paper, covered with PP film, and subjected to XRF (X-ray fluorescence) analysis under the following conditions. Measurement conditions EZ Scan Mode Measuring elements: F~U Measurement time: Standard Measurement diameter: 10mm Balance: None
[0163] [Table 1]
[0164] [Preparation of thermoplastic resin composition and molded article] In each of the Examples and Comparative Examples, the thermoplastic resin and the ferrite particles were mixed in the following amounts. Tuftec H1521 (Asahi Kasei Corporation, hydrogenated styrene-based thermoplastic elastomer) and any of the ferrite particles obtained in Examples 1-11 and Comparative Examples 1-4 were uniformly dry-blended to a composition with a filling rate of 90 wt%, and then the mixture was melt-kneaded in a test kneading device, Labo Plastomill (Toyo Seiki Seisakusho Co., Ltd.), equipped with a small segment mixer KF15V, at a kneading temperature of 240°C and a rotation speed of 33 rpm to obtain a styrene-based thermoplastic elastomer composition.
[0165] The ferrite particle-containing thermoplastic resin composition obtained by the above-mentioned method was injection molded by an injection molding machine IM12 (manufactured by Xplore) at a composition temperature of 240°C, a mold temperature of 80°C, an injection pressure of 15 bar, and a holding pressure of 16 bar to obtain a plate-shaped molded product. The molded product was processed into a shape satisfying an outer diameter of 6.8 to 13.5 mm, an inner diameter of 1.9 to 3 mm, and a thickness of 1.5 to 2.0 mm to obtain a test piece.
[0166] [Preparation of thermosetting resin composition and molded body] A thermosetting resin composition was prepared by mixing KE-109A (two-liquid mixed curing type silicone resin manufactured by Shin-Etsu Chemical Co., Ltd.) and any of the ferrite particles obtained in Examples 1-11 and Comparative Examples 1-24 in a composition with a filling rate of 75 wt% to 85 wt%. The mixture was mixed using a rotation-revolution type kneader.
[0167] The ferrite particle-containing thermosetting resin composition obtained by the above-mentioned method was left to stand in a dryer at 120° C. for 1 hour to be thermally cured, and then formed into a test piece having an outer diameter of 6.8 to 13.5 mm, an inner diameter of 1.9 to 3 mm, and a thickness of 1.5 to 2.00 mm.
[0168] Evaluation The obtained resin compositions and molded articles were evaluated as follows.
[0169] [Evaluation of handling] For thermoplastic resin compositions, a test kneading device, Labo Plastomill (registered trademark, Toyo Seiki Seisakusho Co., Ltd.), equipped with a small segment mixer KF15V was used to calculate and evaluate the average kneading torque value (N·m). A kneading torque value of 44 or less is practically acceptable, 42 or less is more preferable, and 40 or less is particularly preferable. The evaluation results are shown in Table 2.
[0170] For the thermosetting resin composition, a Thinky Mixer (ARV-200, manufactured by Thinky Corporation) was used to visually evaluate whether or not the composition was kneaded properly. If the ferrite particles were not agglomerated and the composition was kneaded uniformly, the result was rated as "Good." If the composition was kneaded properly but agglomerates of the ferrite particles were visible or the viscosity was too high, the result was rated as "Good." If some of the ferrite particles remained in the container without being mixed as powder, or the powder fell out of the composition after it was removed from the container, the result was rated as "Poor." The evaluation results are shown in Table 3.
[0171] [Magnetic permeability measurement] The permeability was measured using a network analyzer (Keysight Technologies, Inc.; E5071C type) and a shielding effect measurement system (Keycom Corporation; GPC7). The test piece obtained above was used as the measurement sample. The measurement was performed with an amplitude of 100 mV, and the frequency range of 500 MHz to 18 GHz was swept on a linear scale to measure the imaginary component μ″ of the complex permeability. If the imaginary component μ″ of the complex permeability is 0.5 or more at 1.5 GHz or 0.2 or more at 7.0 GHz, there is no practical problem, and it is more preferable that it is 1.6 or more at 1.5 GHz or 0.3 or more at 7.0 GHz, and particularly preferable that it is 1.7 or more at 1.5 GHz or 0.4 or more at 7.0 GHz. The evaluation results of the imaginary component μ″ of complex permeability at 1.5 GHz are shown in Table 4. In the table, "-" indicates that the handleability of the obtained resin composition was poor and a test piece could not be prepared, and " / 7GHz" indicates that the imaginary component μ″ of complex permeability at 7 GHz was evaluated.
[0172]
Table 2
[0173]
Table 3
[0174]
Table 4
Claims
1. A x B y C 1-x-y Fe 2 O 4 (wherein 0.3≦x≦0.7, 0≦y≦0.3) The metal elements A, B, and C are each independently one element selected from the group consisting of Ni, Mn, Cu, Zn, Mg, Ca, and Co, and the metal element A is an element different from the metal elements B and C; D of the ferrite particles 50 / D sa Ferrite particles (D sa can be calculated by the following formula (1). D sa = 6 / (specific surface area × specific gravity ρ)… (1)
2. A x B y C 1-x-y Fe 2 O 4 (wherein 0.3≦x≦0.7, 0≦y≦0.3) The metal elements A, B, and C are each independently one element selected from the group consisting of Ni, Mn, Cu, Zn, Mg, Ca, and Co, and the metal element A is an element different from the metal elements B and C; The fine particles adhering to the particle surface of the main particle of the ferrite particle observed from the SEM image (D 50 The ferrite particles are characterized in that the average number of particles having a particle size of 1 / 20 or less relative to the particle size of the ferrite particles is 10 or less.
3. (D 90 -D 10 ) / D 50 The ferrite particles according to claim 1 or 2, wherein the SPAN value obtained by the above calculation is 0.7 or more and 2.0 or less.
4. The ferrite particles according to claim 1 or 2, wherein the ferrite particles have a spinel structure and are polyhedral in shape.
5. D of the ferrite particles 50 The ferrite particles according to claim 1 or 2, wherein the average particle diameter is 0.1 μm or more and 100 μm or less.
6. A method for producing ferrite particles according to claim 1 or 2, As a fluxing agent, D 90 A method for producing ferrite particles, comprising using a molybdate compound having a particle size of 1 to 100 μm in an amount of 50 mass% or less based on the total amount of raw materials.
7. A resin composition comprising the ferrite particles according to claim 1 or 2.
8. The resin composition according to claim 7, wherein the filling rate of the ferrite particles is 75 wt % or more.
9. The resin composition according to claim 8, wherein the imaginary component μ″ of the complex permeability at a frequency of 1.5 GHz is 1.3 or more, or the imaginary component μ″ of the complex permeability at a frequency of 7.0 GHz is 0.4 or more.
Citation Information
Patent Citations
Ni-Zn-BASED FERRITE POWDER, GREEN SHEET CONTAINING THE Ni-Zn-BASED FERRITE POWDER AND Ni-Zn-BASED FERRITE-SINTERED COMPACT
JP2007145703A
Ferrite particles, and carrier for electrophotography and developer for electrophotography using the same
JP2016118646A
Ferrite powder and method for producing the same
JP2021066648A